Correlations Between Working Memory Impairment and Neurometabolites of the Prefrontal Cortex in Drug-Naive Obsessive-Compulsive Disorder - Yue J (Dove Medical Press, 2021)
Jihui Yue,1,2,* Shuming Zhong,1,* Aimin Luo,3 Shunkai Lai,1 Tingting He,4 Yuchong Luo,2 Ying Wang,5 Yiliang Zhang,1 Shiyi Shen,4 Hui Huang,4 Shenglin Wen,2 Yanbin Jia1 1Department of Psychiatry, First Affiliated Hospital, Jinan University, Guangzhou, Guangdong Province, People’s Republic of China; 2Department of Psychiatry, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong Province, People’s Republic of China; 3Department of Psychology, Guangdong Sanjiu Brain Hospital, Guangzhou, Guangdong Province, People’s Republic of China; 4School of Management, Jinan University, Guangzhou, Guangdong Province, People’s Republic of China; 5Medical Imaging Center, First Affiliated Hospital, Jinan University, Guangzhou, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanbin JiaDepartment of Psychiatry, First Affiliated Hospital, Jinan University, Guangzhou, People’s Republic of ChinaTel +86 13392489168Fax +86 020-38688888Email Yanbinjia2006@163.comPurpose: This study aimed to investigate the mechanism of working memory (WM) impairment in drug-naive obsessive-compulsive disorder (OCD) by using neuropsychological tests and proton magnetic resonance spectroscopy (1H-MRS).Patients and Methods: A total of 55 patients with drug-naive OCD and 55 healthy controls (HCs) were recruited for this study. The working memory (WM) was evaluated using the digit span test (DST), visual space memory test (VSMT), and the 2-back task and stroop color word test (SCWT). The bilateral metabolite levels of the prefrontal cortex (PFC) were evaluated by 1H-MRS, then determined the ratios of N-acetyl aspartate (NAA), choline-containing compounds (Cho), and myo-inositol (MI) to creatine (Cr). The independent sample t-test was used to analyse the differences in WM performance and neurometabolite ratios. Multivariate linear regression analysis was performed to screen the influential factors of WM, with an introduction level of 0.05 and a rejection level of 0.10.Results: 1) Patients with OCD performed significantly worse on DST (score), VSMT (score), 2-back task (accuracy rate), SCWT (execution time) when compared with HCs. 2) NAA/Cr and Cho/Cr in the left PFC (lPFC) and MI/Cr ratios in the bilateral PFC of OCD patients were significantly lower when compared to HCs. 3) For OCD patients, the NAA/Cr ratio in the lPFC was negatively correlated with the score of DST (forwards), the Cho/Cr ratio in the lPFC was positively correlated with the accuracy rate of 2-back task, and the MI/Cr ratio in the right PFC (rPFC) was positively correlated with the score of DST (forwards) and the accuracy rate of VSMT. We also found that the compulsive symptoms showed a positive correlation with MI/Cr ratio of the rPFC.Conclusion: Drug-naive OCD patients have demonstrated WM impairments, including phonological loop, visual-spatial sketchpad and central executive system, and the WM impairments might be associated with hypometabolism in the PFC, especially the lPFC.Keywords: obsessive compulsive disorder, prefrontal cortex, working memory, neurometabolites, proton magnetic resonance spectroscopy